Japanese encephalitis virus associated post-infectious relapsing acute onset chronic demyelinating polyradiculoneuritis - Kumar, Aiswarya G.; Arulnambi, Thamil Pavai; L. A., Ravi; Devireddy, Prasoona (International Journal of Research in Medical Sciences, 2023)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an uncommon manifestation of Japanese encephalitis (JE) virus infection. JE is a neurotropic viral tropical disease affecting both CNS and PNS. Hereby report a case of acute onset CIDP (A-CIDP) following primary infection with JE who presented as symmetric flaccid areflexic sensorimotor quadriparesis with subsequent clinical improvement with steroids and plasmapheresis.